2014
DOI: 10.3390/nu6125583
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Intestinal Bacteria Overgrowth in Obesity-Related Nonalcoholic Fatty Liver Disease

Abstract: Nonalcoholic fatty liver disease (NAFLD) is the most common chronic liver disease worldwide. It is a progressive disorder involving a spectrum of conditions that include pure steatosis without inflammation, nonalcoholic steatohepatitis (NASH), fibrosis and cirrhosis. The key factor in the pathophysiology of NAFLD is insulin resistance that determines lipid accumulation in the hepatocytes, which may be followed by lipid peroxidation, production of reactive oxygen species and consequent inflammation. Recent stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
84
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(86 citation statements)
references
References 72 publications
(150 reference statements)
1
84
0
1
Order By: Relevance
“…The data from animal studies support the concept that the gut bacteria may contribute to NAFLD via multiple mechanisms (Table 1), including regulation of energy homeostasis [6, 7] with the increased fermentation of carbohydrates to short chain fatty acids (SCFAs) and subsequent stimulation of de novo synthesis of triglycerides in the liver [8, 9]; modulation of endocannabinoid system [10, 11]; modulation of choline metabolism (which is required for very-low-density lipoprotein synthesis and hepatic lipid export) [12, 13]; modulation of bile acid homeostasis [14, 15]; the ability to generate endogenous ethanol [16, 17]; and bacteria-derived toxins (e.g., lipopolysaccharides (LPS)), which may activate pro-inflammatory cytokine production in the liver macrophages resulting in hepatocellular inflammation [4]. Small intestine bacterial overgrowth (SIBO) has also been linked to NASH pathogenesis [18, 19] [20]. The gut microbiota may also contribute to hepatic fibrosis via stimulation of Toll-like receptor (TLR)-9-dependent profibrotic pathways in hepatic Kupffer cells [21].…”
Section: Introductionmentioning
confidence: 99%
“…The data from animal studies support the concept that the gut bacteria may contribute to NAFLD via multiple mechanisms (Table 1), including regulation of energy homeostasis [6, 7] with the increased fermentation of carbohydrates to short chain fatty acids (SCFAs) and subsequent stimulation of de novo synthesis of triglycerides in the liver [8, 9]; modulation of endocannabinoid system [10, 11]; modulation of choline metabolism (which is required for very-low-density lipoprotein synthesis and hepatic lipid export) [12, 13]; modulation of bile acid homeostasis [14, 15]; the ability to generate endogenous ethanol [16, 17]; and bacteria-derived toxins (e.g., lipopolysaccharides (LPS)), which may activate pro-inflammatory cytokine production in the liver macrophages resulting in hepatocellular inflammation [4]. Small intestine bacterial overgrowth (SIBO) has also been linked to NASH pathogenesis [18, 19] [20]. The gut microbiota may also contribute to hepatic fibrosis via stimulation of Toll-like receptor (TLR)-9-dependent profibrotic pathways in hepatic Kupffer cells [21].…”
Section: Introductionmentioning
confidence: 99%
“…The diagnosis of small intestinal bacterial overgrowth (SIBO) is applied to patients when the concentration of bacteria exceeds 10 5 organisms per milliliter in the jejunum and ileum 33, 34. Not surprisingly, patients with SIBO have increased circulating levels of bacterial endotoxin 35, 36…”
Section: Bacterial Endotoxin In Relation To Chiropractic Practicementioning
confidence: 99%
“…Third, patients who suffer from postprandial abdominal bloating that occurs within 1 hour of eating could be considered “toxic.” In the absence of gluten sensitivity, celiac disease, or other gastrointestinal tract pathologic conditions, the most common cause of such bloating is the fermentation of consumed carbohydrates by an overgrown small intestine bacterial population,32, 49 which leads to endotoxemia 35, 36. Postprandial bloating is an almost universal symptom in patients with irritable bowel syndrome 32 .…”
Section: Measuring Bacterial Endotoxin Levelsmentioning
confidence: 99%
“…The authors concluded that visceral adipose contributing to overall lipidome was secondary to that of other sources of the drainage into the hepatic portal system, for example, the gut. While this is by no means a novel suggestion in the field of NASH [5][6][7], the exact mechanism of this contribution has yet to be demonstrated.…”
mentioning
confidence: 92%
“…It is evident that the changes in the lipid profiles within the liver, the adipose tissue and the plasma, accompany NAFLD, however, the contribution of these changes to the pathogenesis of this disease remain enigmatic [5]. In the current paper titled ''Circulating phospholipid profiling identifies portal contribution to NASH signature in obesity,'' Anjani and colleagues used mass spectrometry-based lipidomic analysis to dissect this so-called Non-Alcoholic Steatohepatitis (NASH) ''signature'' in a cohort of 46 morbidly obese women.…”
mentioning
confidence: 99%